Unlucky migrants: Scarring effect of recessions on the assimilation of the foreign born - Gabriele Lucchetti; Alessandro Ruggieri (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
This paper studies how aggregate labor market conditions affect the intragenerational assimilation of immigrants in the hosting country. Using data from the American Community Survey, we leverage variation in the forecast errors for national and local unemployment rates in the US at the time of arrival of different cohorts of immigrants to identify short- and long-run effects of recessions on their careers. We document that immigrants who enter the US when the labor market is slack face large and persistent earnings reductions: a 1 p.p. rise in the unemployment rate at the time of migration reduces annual earnings by 3.9 percent on impact and 1.4 percent after 12 years since migration, relative to the average US native. This effect is not homogeneous across migrants: males without a college education from low-income countries are the only ones who suffer a scarring effect in their assimilation path. Change in the employment composition across occupations with different skill contents is the key driver: were occupational attainment during periods of high unemployment unchanged for immigrants, assimilation in annual earnings would slow down on average by only 3 years, instead of 12. Slower assimilation costs between 1.7 and 2.5 percent of lifetime earnings to immigrants entering the US labor market when unemployment is high.
Keywords: E32; J15; J31; J61; 330; immigration; earnings assimilation; low-skill jobs; business cycle